Analisis pendapatan pengepul ayam kampung di Kecamatan Anjir Pasar Barito Kuala: Income analysis of local breed chicken collectors in Anjir Pasar Barito Kuala District - Sugiarti, Sugiarti; Rostini, Tintin; Nurawaliyah, Siti (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2024)
Abstract The aim of this study was to analyze the income of local breed chicken collectors at Anjir Market in Anjir Pasar District, Barito Kuala Regency, South Kalimantan Province. Respondents in this study were 8 local breed chicken collectors located at Anjir Market in Anjir Pasar District, Barito Kuala Regency, totaling 8 people where the determination was determined purposively, namely all local breed chicken collectors. The data collected in this study are primary data and secondary data. Primary data was obtained through interviews with collectors using a questionnaire while secondary data was obtained from related parties. The data obtained from the survey was tabulated and then the income of native chicken seller and the R/C ratio were calculated. The results showed that there were 2 marketing channels for local breed chicken collectors, namely: Collectors to onsumers and collectors to Big Collector to consumer. The highest income of local breed chicken seller is IDR 2,574,000 per month and the lowest is IDR 699,000 per month with an average of IDR 1,361,500 per seller per month with the highest R/C value of 1.20 and the lowest 1.09 with an average of 1.14. The overall R/C is greater than 1, so selling local breed chicken is profitable. Keywords: Collectors; Income analysis; Local breed chicken Abstrak Penelitian bertujuan untuk menganalisis pendapatan pengepul ayam kampung yang ada di Pasar Anjir di Kecamatan Anjir Pasar, Kabupaten Barito Kuala, Provinsi Kalimantan Selatan. Responden dalam penelitian ini adalah pengepul ayam kampung yang berada Pasar Anjir di Kecamatan Anjir Pasar, Kabupaten Barito Kuala yang berjumlah 8 orang dimana penentuan ditentukan secara purposif yaitu seluruh pengepul ayam kampung. Data yang dikumpulkan dalam penelitian ini adalah data primer dan data sekunder. Data primer diperoleh melalui wawancara dengan pengepul menggunakan kuisioner sedangkan data sekunder diperoleh dari pihak – pihak terkait. Data yang diperoleh dari survei ditabulasi kemudian dihitung pendapatan pedagang ayam kampung dan R/C rasio. Hasil penelitian menunjukkan bahwa Saluran pemasaran pedagang pengepul ayam kampung ada 2 yaitu: Pengepul ke konsumen dan Pengepul ke Pengepul Besar ke konsumen. Pendapatan pedagang ayam kampung tertinggi Rp 2.574.000 per bulan dan terendah Rp 699.000 per bulan dengan rata-rata Rp 1.361.500 per pedagang per bulan dengan nilai R/C tertinggi 1,20 dan terendah 1,09 dengan rata-rata 1,14. R/C secara keseluruhan lebih besar dari 1, sehingga berdagang ayam kampung menguntungkan. Kata kunci: Ayam kampung; Pendapatan; Pengepul ayam kampung